Analisis Kinerja Mesin Welding dengan Menggunakan Metode Overall Equipment Effectiveness (OEE) Pada Divisi Alat Berat di PT. XY - Aldha, Aldha; Nugraha, Asep Erik (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
XY is a manufacturing industry engaged in the production of defense equipment. In the production process, machines are one of the important things. As one of the most important aspects in the manufacturing process, machine productivity must always be improved. Therefore, methods are needed to increase productivity in line with fluctuating business needs. Overall Equipment Effectiveness (OEE) is a method that can be used to determine the productivity of a machine. OEE is related to the availability ratio, performance ratio, and quality ratio of the production process. The multiplication of these three factors produces the company's OEE value which will later be compared with the Japan Institute of Plant Maintenance (JIPM) standard OEE value. Research was carried out on welding machines at PT. XY. The machine is used to make bumpers. Based on calculations, the welding machine obtained an availability ratio (83%), quality ratio (100%) and performance efficiency (87%). So, if the three are multiplied, we get an OEE value of 72%, it can be seen that the OEE value is still below the global standard of 85%. Keywords: Availability Ratio, Overall Equipment Effectiveness (OEE), Performance Ratio, Quality Ratio, Welding Machine